Degree-Based Topological Indices of Polysaccharides: Amylose and Blue Starch-Iodine Complex - Anam Rani; Usman Ali (Journal of Chemistry)
Starch is a polymer of glucose where alpha-linkages are associated with glucopyranose units. It comprises a mixture of amylose and amylopectin. Furthermore, amylose is a linear chain of hundreds of glucose molecules. Starches are not allowed to be dissolved in water. They can be digested by breaking down alpha bonds (glycosidic bonds). Its cyclic degradation products, called cyclodextrins, are the best role models for amylose. They can be considered simple turns of the amylose propeller that has imploded into a circular path. Both humans and animals have amylases, which allow them to digest starches. The important sources of starch include potatoes, rice, wheat, and maize for human consumption. The production of starches is how plants store glucose. The blue colour of starch produced by an iodine solution or iodine reaction is used for its identification. Polysaccharides with a reduced degree of polymerization, known as dextrins, are produced in the starch’s partial acid hydrolysis. Complete hydrolysis leads to glucose. In this article, we compute the topological properties: Zagreb index M1Γ and M2Γ, Randić index RαΓ for α=−1/2,−1,1/2,1, atom-bond connectivity index ABCΓ, geometric-arithmetic index GAΓ, fourth atom-bond connectivity index ABC4Γ, fifth geometric-arithmetic index GA5Γ, and degree-based topological indices of a graph Γ representing polysaccharides, namely, amylose and blue starch-iodine complex. In the end, we compare these indices and depict their graphic behavior.